Ethnic conflicts in Lebanon - Stefanović Dina; Grubić Goran (Војно дело, 2015)
The paper deals with ethnic and religious conflicts in Lebanon, particularly focusing on the impact of external forces and religious teachings on the course and intensity of the violence. At the beginning the paper examines the role of religion in conflicts and roots of ethno-religious conflicts in Lebanon. Then, it discusses the factions and the participants in the civil war, as well as the key external factors that led to the transformation of the civil war into a prolonged international conflict. The final section of the paper summarizes the factors that led to the change in the situation after 2000, and presents the current inter-ethnic and inter-religious situation in Lebanon, with an overview of the prospects of further development. Apart from considering the immanent factors of inter-ethnic and inter-religious conflict in Lebanon, the paper emphasizes the role of external forces and international conflicts in contributing to the internal fragmentation of Lebanese society.